Barbados : 2021 Article IV Consultation, Sixth Review Under the Extended Arrangement Under the Extended Facility, and Request for Modification of Performance Criteria-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
While Barbados has been making good progress in implementing its Economic Recovery and Transformation (BERT) plan to restore fiscal and debt sustainability, rebuild reserves, and increase growth, it continues to face major challenges owing to the global pandemic. International reserves have increased to USD 1.4 billion by October 2021 supported by IFI loans. This, and a successful 2018-19 public debt restructuring, have helped rebuild confidence in the country's macroeconomic framework. However, a virtual standstill in the tourism sector during the pandemic took a significant toll in 2020, with the economy contracting by 18 percent. While Barbados was successful in containing the outbreak during 2020, renewed COVID-19 waves weighed on the economic recovery in 2021. In addition, Barbados was hit by the twin natural disaster shocks of volcanic ashfalls from neighboring St. Vincent in April and category 1 hurricane Elsa in July. Economic growth is projected at 1.6 percent for 2021 premised on a modest recovery of tourism towards the end of 2021-down from 3 percent projected at the time of the fifth EFF review. The outlook remains highly uncertain, and risks are elevated.